2021
DOI: 10.1155/2021/6696733
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fullerene C60 to Preserve Testicular Tissue after Cryopreservation

Abstract: Autologous transplantation of cryopreserved fragments of an immature testis is an actively developing approach to save fertility in patients facing a gonadotoxic therapy. The use of bioavailable fullerene C60 as a powerful antioxidant opens up a new potential for the prevention and correction of ischemic-reperfusion pathological processes in tissues including those associated with freezing-thawing procedure. In this work, we aimed to study the antioxidant status, apoptotic/necrotic processes, and morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The binding ability of C 60 HyFn mainly to the mitochondria in the cell (Foley et al, 2002) is important for the protection of mitochondria, which are extremely sensitive to oxidative damage (Rajender et al, 2010). In a recent study (Volkova et al, 2021), C 60 HyFn has also been reported to prevent the decrease in the activity of mitochondria during cryopreservation of testicular tissue. In this study, the addition of 800 nM C 60 HyFn significantly increased the percentage of sperm with highly active mitochondria in…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The binding ability of C 60 HyFn mainly to the mitochondria in the cell (Foley et al, 2002) is important for the protection of mitochondria, which are extremely sensitive to oxidative damage (Rajender et al, 2010). In a recent study (Volkova et al, 2021), C 60 HyFn has also been reported to prevent the decrease in the activity of mitochondria during cryopreservation of testicular tissue. In this study, the addition of 800 nM C 60 HyFn significantly increased the percentage of sperm with highly active mitochondria in…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, it is emphasized that C 60 HyFn reduces apoptosis by inactivating caspases, whereas C 60 dissolved in tetrahydrofuran solution increases apoptosis by activating caspases, so the effects of C 60 solvents on apoptosis are very important (Harhaji et al., 2008). In a recent study, C 60 HyFn has been reported to reduce the release of cytochrome C, which leads to caspase activation during cryopreservation of testicular tissue (Volkova et al., 2021). In this study, the addition of all C 60 HyFn concentrations significantly reduced DNA fragmentation and caspase‐3 activation in frozen–thawed ram semen compared to control.…”
Section: Discussionmentioning
confidence: 99%